Bevardės giminės dalyvių konstrukcijos su kiekybinės reikšmės junginiais bendrinėje lietuvių kalboje ir jų atitikmenys latvių kalboje - Valskys, Vidas (Kalbotyra, 2004)
This article makes a synchronic analysis of neutergender participial constructions with constructs having the meaning of quantity in Standard Lithuanian. The article also analyses the syntactic and semantic functions of the constructions. The structure of neutergender participial constructions with constructs having the meaning of quantity is compared with other syntactic models. The analysed constructions of Lithuanian are also contrasted with their equivalents in Latvian, which belongs to the same stock.